2020
DOI: 10.1101/2020.08.22.262451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Light-emitting diode-based transcranial photoacoustic measurement of sagittal sinus oxyhemoglobin saturation in hypoxic neonatal piglets

Abstract: We present a light-emitting diode (LED)-based transcranial photoacoustic measurement (LED-trPA) of oxyhemoglobin (HbO2) saturation at superior sagittal sinus (SSS) in hypoxic neonatal piglets. The optimal LED imaging wavelengths and frame averaging scheme were determined based on in vivo characterization of transcranial sensitivity. Based on the framework (690/850 nm with >20 frame averaging), graded hypoxia was successfully identified in neonatal piglets in vivo with less than 10.0 % of root mean squared e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…High laser intensity yields deeper imaging depth with exponential attenuation, but the traditional approach would raise a safety concern for patients. Our longterm goal is to transform our transcranial PA imaging system into a safer, compact, and cost-effective form factor, based on promising progress with a compact light source (pulse laser diode [44], lightemitting diode [28], etc). Such types of light sources provide much more abundant temporal information than that given with conventional high-energy laser sources (1-10 kHz vs. 10-20 Hz), enabling novel signal processing algorithms for augmenting the desired signal sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High laser intensity yields deeper imaging depth with exponential attenuation, but the traditional approach would raise a safety concern for patients. Our longterm goal is to transform our transcranial PA imaging system into a safer, compact, and cost-effective form factor, based on promising progress with a compact light source (pulse laser diode [44], lightemitting diode [28], etc). Such types of light sources provide much more abundant temporal information than that given with conventional high-energy laser sources (1-10 kHz vs. 10-20 Hz), enabling novel signal processing algorithms for augmenting the desired signal sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical applications using PA technology have been proposed [16][17][18][19][20][21][22][23], and hemodynamic imaging has been a primary clinical application with stark hemoglobin absorbance, enabling quantifications of blood oxygen saturation and cerebral blood volume [24][25][26]. Transcranial PA sensing of physiological change at the superior sagittal sinus (SSS) has been demonstrated in the neonatal piglet and ovine models through intact scalp [27][28][29], but there is still room for further development to have physiological measures in brain tissue, wherein the concentration of hemoglobin is an order of magnitude less than in the sagittal sinus vein. J Lv, et al also demonstrated transcranial PA imaging of structural and functional dynamics in rodent brain during ischemic stroke at a very early stage (from 5 min to 6 h onset) [30], but the implication for clinical translation is still limited by the use of the rodents with impractical imaging scale and small signal attenuation with its very thin skull layer.…”
Section: Introductionmentioning
confidence: 99%
“…Our long-term goal is to transform our transcranial PA imaging system into a safe, compact, and cost-effective form factor to facilitate its clinical translation. The investigation should be based on promising progress in compact light source (pulse laser diode [40], light-emitting diode [25], etc.) and ultra-portable ultrasound imaging systems [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical applications using PA technology have been proposed [16][17][18][19][20], and hemodynamic imaging has been a primary clinical application with stark hemoglobin absorbance, enabling quantifications of blood oxygen saturation and cerebral blood volume [21][22][23]. Transcranial PA sensing of physiological change at the superior sagittal sinus (SSS) has been demonstrated in the neonatal piglet and ovine models through intact scalp [24][25][26], but there is still room for further development to have physiological measures in brain tissue, wherein the concentration of hemoglobin is an order of magnitude less than in the sagittal sinus vein. J. Lv, et al also demonstrated transcranial PA imaging of structural and functional dynamics over rodent brain during ischemic stroke at a very early stage (from 5-min to 6-hour onset) [27], but the implication for clinical translation is still limited by the use of the rodents with impractical imaging scale and small signal attenuation with its very thin skull layer.…”
Section: Introductionmentioning
confidence: 99%